Kajian Literatur : Faktor Yang Mempengaruhi Turnover Intention Karyawan Dalam Manajemen Sumber Daya Manusia - Idam Wahyudi; Auliya Nurmalasari; Bikorin Bikorin; Muhammad Akmal; Yoshua Ronaldo Primartono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to conduct a literature review on previous research related to factors influencing employee turnover intention in human resource management. This research falls under the category of library research,. The analysis of theory and relationships between variables is carried out through journals obtained from sources such as Publish or Perish, Mendeley, Google Scholar, and e-books. The findings of the research indicate that employee competency levels have a positive impact on turnover intention, indicating that despite possessing high skills, factors such as employee motivation, salary satisfaction, and organizational climate also play a significant role in influencing turnover intention. Furthermore, work stress, organizational commitment, and job satisfaction were identified as factors having a negative impact on turnover intention. The study also underscores that a positive organizational culture can diminish turnover intention, emphasizing the need to consider other variables such as work environment, leadership style, and organizational commitment. Additionally, the research highlights emotional labor and burnout as significant factors, wherein heightened emotional exhaustion can amplify employees' inclination to leave their jobs. Subsequent research endeavors could explore contextual factors that may moderate or alter the relationship between the identified variables (such as competence, motivation, job satisfaction) and turnover intention.